Pemanfaatan Lilin Aromaterapi Berbahan Dasar Sereh Sebagai Strategi Pencegahan DBD Di Desa Puasana, Kecamatan Moramo Utara, Kabupaten Konawe Selatan - Effendy, Devi Savitri; Haliza, Nur; Damayanti, Novi; Putri, Amelia; Yuniar, Nani; Harleli; Lestari, Hariati; Bahar, Hartati; Prasetya, Fikki (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Dengue fever is a disease that kills a lot of people and attacks the community, so it's important to pay attention to this intense outbreak. Different endeavors have been made to defeat this episode, yet there are as many individuals who don't know about the dangers. Aromatherapy candles are one option for repelling mosquitoes. Aromatherapy candles can be made from the abundant lemongrass that grows in the yard. Aromatherapy candles with lemongrass in them repel mosquitoes and can help alleviate stress. This act of community service involves teaching members of the community, particularly cadres in Puasana village, about the dangers of dengue fever and how to get it. In addition to counseling, instructions were given on how to make aromatherapy candles. In this way, people will learn more about the dangers of dengue fever and how living plants can be turned into valuable objects